A new SMA mix design approach for optimisation of stone-on-stone effect - Henrique Manuel Borges Miranda (2019)
Traditionally Stone Mastic Asphalt (SMA) is empirically designed, which could not guaranty an adequate stone-on-stone effect. To overcome this drawback, a research study was carried out having in view to develop a new SMA mix design approach for the optimisation of the stone-on-stone effect, based on new findings. To this end, the study included not only the evaluation of volumetric characteristics of SMA test specimens, but also the characteristics of coarse aggregates (CA) test specimens, prepared using different aggregate compaction methods: (i) bulk particles' specimens (compaction not applied), (ii) dry-rodded compaction, (iii) Proctor compaction and (iv) steel roller compaction. Bituminous mixtures' specimens were prepared by impact compaction using the Marshall compactor. In this context, the following test specimens' characteristics were assessed: air void content of compacted coarse aggregates (VCA), void in the coarse aggregate of compacted SMA (VCA(MIX)), air void content (porosity, Vv), voids filled with bituminous binder (VFB) and workability of nine different SMA. Results showed that pre-established grading envelopes did not allow the design or optimisation of the stone-on-stone effect. On the other hand, the new analytical mix design approach, complemented by the coarse aggregate Proctor compaction (55 blows per each layer, in a total of 5 equal layers), provides an alternative to current SMA mix design methods, since it: (i) is easy and cheap to perform, (ii) is time less consuming, and (iii) allows to obtain an air void and particle breakage more similar to the field.